Fungsi Sosial Tradisi Molebingga dalam Kehidupan Masyarakat Rote Dengka - Tasya Eoh Ndolu; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to describe the implementation anf social meaning of the Molebingga tradition on the Rote Dengka community and to explain its function in strengthening social solidarity amid modernization. A qualitative approach with a libraray research method was used by analyzing written sources about Rote culture, the Molebingga tradition, and theories of social function and solidarity. Data were analyzed deescriptively to identify the social value embedded in the ritual. The results showed that Molebingga was not merely a post-funeral ritual but also a medium for social recovery, kinship reinforcement, and value education for younger generations. The social values reflected in the tradition include kinship responsibility, solidarity, empathy, mutual cooperation, and moral-emotional restoration. This tradition function to maintain social harmony and stengthen community unity in Rote Dengka depite social changes. The study recommended involving young generations and applying educational approaches to preserve the social values of Molebingga as a culturally relevant heritage for modern life